POLITICAL PARTICIPATION IN VILLAGE HEAD ELECTIONS IN JEBLOG, BLITAR DISTRICT - Muhammad Iqbal Baihaqi; Luthfia Amalia Syafrida (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2023)
The election of the village head is a political activity that shows how the process of democracy occurs in the village. Pilkades cannot be separated from the development of political dynamics that occur in the village. The background to this research is the simultaneous village elections that took place in Blitar district 2022. One of the things studied was in Jeblog village, Blitar district regarding political participation and the economic impact felt by the community from the election of the village head. The results of this study are that there is politics in every election which has become normal for the community and there is no economic impact from the election of this village head, both from the previous government and the one to be elected. Because in this pilkades, the village does not hold large-scale events or campaigns so that the community will not socialize the vision and mission of each candidate and only know word of mouth. .